Assessing the impact of limiting Indonesian palm oil exports to the European Union - Amzul Rifin; Feryanto; Herawati; Harianto Harianto (Journal of Economic Structures, 2020)
The latest challenge faced by the Indonesian palm oil industry concerns the Delegated Act that has been adopted to limit the use of palm oil in biofuels because palm oil is considered to not support the sustainable development program. The objective of this article is to assess the suspension of Indonesia's palm exports to the European Union in terms of Indonesia's economic conditions. The Global Trade Analysis Project (GTAP) model is used to assess the impact, and the results indicate that the suspension will not create significant impacts on the economic growth, GDP, macro-welfare, and exports and imports of Indonesia.
Keywords: 330; Palm oil; European Union; Import